Hip Arthroscopic Management for Femoral Head Fractures and Posterior Acetabular Wall Fractures (Pipkin Type IV) - Myung-Sik Park, M.D.; Sun-Jung Yoon, M.D.; Seung-Min Choi, M.D. (Arthroscopy Techniques, 2013)
Femoral head fractures associated with acetabular fractures are usually treated by an open method. After a closed reduction of a hip dislocation, open reduction and internal fixation of acetabular fractures usually depend on the type of acetabular fracture. Acetabular fractures associated with femoral head fractures, torn labrums, or osteochondral fractures are often managed simultaneously by a posterior approach. The patient in this study was referred to us because of pain and limited motion after open reduction and internal fixation of an acetabular fracture. Postoperative computed tomography showed remnant osteochondral fragments located in the cotyloid fossa. Using hip arthroscopy, we found a torn labrum and multiple osteochondral fragments in the cotyloid fossa. The avulsed torn labrum was reattached with 2 anchors through the midanterior portal. Osteochondral fragments were curetted and removed. This article reviews the treatment of the torn labrum and multiple fragments after acetabular fracture reduction. The patient recovered immediately and had a satisfactory outcome. We conclude that hip arthroscopy is a valuable option for treating femoral head fracture dislocations associated with acetabular fractures.